2022
DOI: 10.1111/cob.12546
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss with glucagon‐like peptide‐1 receptor agonists in Bardet‐Biedl syndrome

Abstract: Summary Bardet–Biedl syndrome (BBS) is a rare genetic condition, characterized by ciliary protein dysfunction, leading to multi‐organ damage. People with BBS can develop early‐onset severe obesity and associated problems including the metabolic syndrome, type 2 diabetes and coronary heart disease. Weight management can be challenging with the lack of effective medical therapies so far. We report a patient with BBS who underwent successful weight reduction through the use of glucagon‐like peptide‐1 receptor ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…It was necessary to maintain the drug in therapy, because it was observed a weight regain after dose reduction. 141 Pre-clinical studies demonstrated that the use of roscovitine and rapamycin was able to rescue renal cysts in zebrafish models of BBS. 142 A novel target for therapy in BBS is glycosphingolipid metabolism, in experimental models of disease.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It was necessary to maintain the drug in therapy, because it was observed a weight regain after dose reduction. 141 Pre-clinical studies demonstrated that the use of roscovitine and rapamycin was able to rescue renal cysts in zebrafish models of BBS. 142 A novel target for therapy in BBS is glycosphingolipid metabolism, in experimental models of disease.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…61 There is one case report of successful weight loss with GLP-1RA therapy in a 28-year-old female with BBS and type 2 diabetes. 62 In our clinical experience, GLP-1RAs are not effective at appetite suppression in this population.…”
Section: Management Of Obesitymentioning
confidence: 81%
“…Glucagon-like peptide-1 receptor agonists (GLP-1 RA) have also been considered as a weight management treatment in hyperphagic obesity syndromes [26]. Thus far, these drugs have limited evidence of effectiveness to treat hyperphagia or obesity in people with BBS [27 ▪ ]. Given their role in the treatment of obesity and hyperglycaemia (including type 2 diabetes mellitus) in other populations, investigation of the effectiveness of GLP-1 RAs merit further investigation.…”
Section: Discussionmentioning
confidence: 99%